First results of the tracking system calibration of the TAIGA-IACT telescope - Zhurov, D.; Gress, O.; Sidorov, D.; Astapov, I.; Bezyazeekov, P.; Boreyko, V.; Borodin, A.; Budnev, N.; Brueckner, M.; Chiavassa, A.; Dyachok, A.; Fedorov, O.; et al. (Journal of Physics: Conference Series, 2019)
n/a